Prevalence of Sonographic Markers of Placenta Accreta Spectrum in Low-Risk Pregnancies - Philips, Jennifer; Gurganus, Margot; DeShields, Sarah; Cunningham, Tina; Sinkovskaya, Elena; Kanaan, Camille; Porche, Lea; Abuhamad, Alfred (American Journal of Perinatology, 2019)
Objective This study was aimed to evaluate the prevalence of sonographic markers for placenta accreta spectrum (PAS) in pregnancies at low-risk for PAS.Study Design Pregnant women at low-risk for PAS presenting for routine second trimester ultrasound who enrolled in the study were evaluated prospectively for sonographic markers of PAS during two ultrasounds at 18 to 24 and 28 to 34 weeks. Frequencies of PAS markers were compared between the second and third trimester and between those with and without prior cesarean deliveries (CD).Results Overall, 174 women were included. Several markers were seen frequently in the second trimester: vascular cervical invasion (57%), lacunae (46%), subplacental hypervascularity (37%), and irregularity of the posterior bladder wall (37%). Other markers were seen infrequently or not at all: loss of the retroplacental clear zone, uterovesical interface < 1 mm, bridging vessels, placental bulge or focal exophytic mass. Frequencies of markers did not differ between women with and without prior CD. Lacunae were larger and more numerous in the third trimester. Two or more PAS markers were observed in 98% of second trimester ultrasounds.Conclusion Several PAS sonographic markers occur commonly in low-risk pregnancies. In the absence of risk factors, the independent predictive value of these markers is questionable.
Keywords: ultrasound; placenta; accreta; low-risk; sonographic markers